Pengaruh budaya organisasi, kepemimpinan, dan grit pada karyawan di salah satu perusahaan property developer di Jakarta - Sahlan Suganda; Mohammad Agung Saryatmo (Universitas Tarumanagara, 2023)
In an era of a growing business, the property development company is currently one of the companies that are able to contribute to the country's economy. This, of course, must be supported by qualified and competent human resources. The purpose of this study is to analyze the influence of organizational culture, leadership, and grit on work engagement in one of the property developer companies in the Jakarta area. This study uses a quantitative type involving 245 respondents. This study applies the analytical method through SmartPLS 4.0 by testing the measurement model assessment and structural model assessment. This research resulted in a trend of significant positive influence on work engagement through leadership and grit. Thus, leadership and grit have factors that can influence employee engagement, so this needs to be considered and improved so that company goals can be achieved. Furthermore, there are findings that work engagement is not influenced by organizational culture. So that the company PT